2020
DOI: 10.1002/saj2.20006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waterlogging and increased salinity on microbial communities and extracellular enzyme activity in native and exotic marsh vegetation soils

Abstract: Coastal ecosystems are vulnerable to plant invasion and expected sea level rise in China. This study explored the responses of microbial communities and extracellular enzyme activity in the marsh soils of native Phragmites australis and exotic Spartina alterniflora to waterlogging and increasing salinity (to mimic prolonged inundation and saltwater intrusion) based on the determination of phospholipid fatty acids and analysis of enzyme kinetics. The results showed that waterlogging and increased salinity treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 90 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…However, these responses were not always consistent for individual studies, indicating that other unknown factors (e.g., hydrologic context) also affect Hy‐C and Ox‐C EEAs. We tried to collect information, such as tidal range, tidal inundation frequency, mean inundation level, or intertidal flat zone, from the published papers, but very few studies provided this information (Chambers et al., 2016; Liu et al., 2021; Xie et al., 2020). The results from published studies showed that increasing flooding did not significantly alter the response of Hy‐C EEAs to salinization (Chambers et al., 2016; Xie et al., 2020), but flooding sometimes reduced the stimulation of Ox‐C EEAs with salinization in tidal wetland systems (Liu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these responses were not always consistent for individual studies, indicating that other unknown factors (e.g., hydrologic context) also affect Hy‐C and Ox‐C EEAs. We tried to collect information, such as tidal range, tidal inundation frequency, mean inundation level, or intertidal flat zone, from the published papers, but very few studies provided this information (Chambers et al., 2016; Liu et al., 2021; Xie et al., 2020). The results from published studies showed that increasing flooding did not significantly alter the response of Hy‐C EEAs to salinization (Chambers et al., 2016; Xie et al., 2020), but flooding sometimes reduced the stimulation of Ox‐C EEAs with salinization in tidal wetland systems (Liu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We tried to collect information, such as tidal range, tidal inundation frequency, mean inundation level, or intertidal flat zone, from the published papers, but very few studies provided this information (Chambers et al., 2016; Liu et al., 2021; Xie et al., 2020). The results from published studies showed that increasing flooding did not significantly alter the response of Hy‐C EEAs to salinization (Chambers et al., 2016; Xie et al., 2020), but flooding sometimes reduced the stimulation of Ox‐C EEAs with salinization in tidal wetland systems (Liu et al., 2021). This might be because the Ox‐C EEAs require oxygen (Freeman et al., 2001; Wang et al., 2017), and increasing inundation will reduce the oxygen availability in wetland soils (Kostka et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The determination method was slightly modified by referring to Xie et al (Chen et al, 2020;Xie et al, 2020). The urease activity was determined by the sodium phenolate colorimetric method, and the invertase and cellulase activities were determined by the 3,5dinitrosalicylic acid colorimetric method.…”
Section: Soil Enzyme Activity Determinationmentioning
confidence: 99%
“…References determination of soil enzyme activity (Xie et al 2020, Chen et al 2020). The urease activity is determined by the sodium phenolate colorimetric method, and the invertase and cellulase activities are determined by the 3,5-dinitrosalicylic acid colorimetric method.…”
Section: Determination Of Soil Propertiesmentioning
confidence: 99%